Analisis Permasalahan Koordinasi Pemerintahan (Tinjauan Konseptual Dan Teoritis) - Febrian, Ranggi Ade (WEDANA: Jurnal Kajian Pemerintahan, Politik dan Birokrasi, 2015)
The problem of coordination is one of the issues most important rule, the more so after the first world war increasingly difficult but also the greater meaning. In governance, coordination becomes a dominant factor several unsuccessful government in carrying out the functions of development, service delivery, and empowerment functions. Ego sectoral owned government institutions, which impressed prestige to work, ask for help or just inquire with other government agencies is a problem of coordination of government. Coordination role has always been the pivot, and guard the balance and smoothness of rotation of the "machine" that there diseputarnya government, for example, coordinating the development of local governance in Indonesia in Indonseia from time to time. Orientation on common goals is one way to reduce sectoral ego and imitate the Prophet Muhammad's leadership in the implementation of government coordination made will be solutions to problems of coordination of government.